An examination of the heat treatment effect on mechanical properties of twin-roll cast followed by cold rolling sheets made of aluminium and its alloys (Metallurgy and Foundry Engineering, 2014)
Modern aluminium alloys are more commonly used in various industries. Often the products of such materials operate at elevated temperatures. In addition to standard requirements in terms of mechanical and technological properties, one of the key performance properties becomes the increased resistance to annealing. This paper examines the heat treatment effect on the mechanical properties of sheets made of aluminium with grain refiner additions (Ti + B), Fe, Si and Mn. Tested materials were obtained by cold-rolling strips, manufactured by twin-roll casting – TRC method. TRC method is increasingly being used in the manufacture of flat-rolled products. This technology eliminates the hot rolling operations and the strip obtained by TRC method can besubjected to direct cold rolling.